Professional Self-Realization as a Factor in the Psychological Well-Being of Specialists of Caring Professions - Glavinska, Olena D.; Ovdiyenko, Irina M.; Brukhovetska, Oleksandra V.; Chausova, Tetiana V.; Didenko, Maryna S. V. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Research Objective: the article discusses the mutual influence of professional self-realization and the psychological well-being of specialists of caring professions. Methodology: correlation and comparative analysis in different professional groups of specialists. The study involved 465 volunteers with work experience of 3 to 40 years: teachers, doctors, medical personnel, psychologists of state and private enterprises. Several standardized self-reports were used to collect data: Ryff’s Scales of Psychological Well-being, Professional Burnout Questionnaire, Kokun’s Professional Self-Fulfilment Questionnaire, Gura’s Workplace Satisfaction Self-assessment Survey, Tkalych’s Work-Life Balance additional scale. The use of the open questions allowed clarifying some phenomenological manifestations of professional self-realization among specialists of caring professions, as well as to clarifying the external and internal determinants of self-realization. The authors tested the hypotheses about the influence of several factors on the level of psychological well-being: belonging to a certain professional group, the degree of self-realization, as well as age, gender, and length of service. The results of the study present the structure of well-being and features of self-realization in different professional groups. We proved that professional self-realization is a significant factor in the formation of individual components of psychological well-being: self-acceptance and competence. However, in some cases, high scores for professional self-realization may be associated with burnout and the desire to leave the job. The conclusions contain recommendations on organizational agency and direct psychological interventions that ensure the psychological well-being of specialists of caring professions.